2016
DOI: 10.3389/fnagi.2016.00174
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Brain Functional Network Architecture in Chronic Tinnitus Patients

Abstract: Purpose: Resting-state functional magnetic resonance imaging (fMRI) studies have demonstrated the disruptions of multiple brain networks in tinnitus patients. Nonetheless, several studies found no differences in network processing between tinnitus patients and healthy controls (HCs). Its neural bases are poorly understood. To identify aberrant brain network architecture involved in chronic tinnitus, we compared the resting-state fMRI (rs-fMRI) patterns of tinnitus patients and HCs.Materials and Methods: Chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 89 publications
3
42
1
Order By: Relevance
“…Rauschecker et al (2010) developed a model to demonstrate structural and functional differences in ventromedial prefrontal cortex that were associated with tinnitus subjective loudness, indicating that frontal cortex may contribute to certain perceptual features of tinnitus. Resting-state fMRI studies have pointed out that the abnormalities of the frontal cortex could act as a direct mechanism of tinnitus chronification (Burton et al, 2012; Schmidt et al, 2013; Chen et al, 2014, 2015c,d, 2016), which are confirmed by the current meta-analysis. Based on the previous fMRI studies, the SFG has been regarded as a major integrative hub of the tinnitus network architecture (Chen et al, 2016), which can receive and integrate all kinds of information from different parts of the brain from inside and outside the body.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Rauschecker et al (2010) developed a model to demonstrate structural and functional differences in ventromedial prefrontal cortex that were associated with tinnitus subjective loudness, indicating that frontal cortex may contribute to certain perceptual features of tinnitus. Resting-state fMRI studies have pointed out that the abnormalities of the frontal cortex could act as a direct mechanism of tinnitus chronification (Burton et al, 2012; Schmidt et al, 2013; Chen et al, 2014, 2015c,d, 2016), which are confirmed by the current meta-analysis. Based on the previous fMRI studies, the SFG has been regarded as a major integrative hub of the tinnitus network architecture (Chen et al, 2016), which can receive and integrate all kinds of information from different parts of the brain from inside and outside the body.…”
Section: Discussionsupporting
confidence: 83%
“…Resting-state fMRI studies have pointed out that the abnormalities of the frontal cortex could act as a direct mechanism of tinnitus chronification (Burton et al, 2012; Schmidt et al, 2013; Chen et al, 2014, 2015c,d, 2016), which are confirmed by the current meta-analysis. Based on the previous fMRI studies, the SFG has been regarded as a major integrative hub of the tinnitus network architecture (Chen et al, 2016), which can receive and integrate all kinds of information from different parts of the brain from inside and outside the body. Besides, it can also timely organize efferent impulses to ensure the coordination of the central nervous system as a whole (Mathiak et al, 2007; Melloni et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In most cases, tinnitus was associated with an increase in effective connectivity rather than a decrease [Chen et al, 2016;Hong et al, 2016;Zobay et al, 2015]. In tinnitus patients, significant changes in effective connectivity occurred in a relatively circumscribed network emanating from and projecting to the amygdala or the hippocampus.…”
Section: Discussionmentioning
confidence: 98%